Pola Dakwah Gerakan Padri di Minagkabau - Maryam Maryam (JURNAL ILMIAH SYI'AR, 2015)
Since the emergence of the movement of clerics in minagkabau, Approximately nearly two centuries at the beginning of 1803, the attention of the Muslim and non-Muslim scholars of the movement was the brainchild of thought H. Poor CS yet to show signs of many scientists, social, economic, historians and theologians. Mention the various attributes given to him, such as the Islamic reform movement, radicalism and Islamic revivalism. Padri This article about this, for it is in this paper, is an attempt to explain the pattern Propagation Padri movement and its impact on the Minagkabau community.